1995
DOI: 10.1016/s0741-5214(95)70219-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous aortic and renal artery reconstruction: Evolution of an eighteen-year experience

Abstract: The current operative mortality rate for AOR is in the range anticipated for aortic surgery alone, and this appears to be related to improved detection and treatment of associated coronary artery disease and intervention before major deterioration in renal function. These findings coupled with currently available natural history data relative to renovascular disease justify an aggressive approach with AOR when significant renal artery stenosis is detected during evaluation of aortic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…14,21,25-27 Several recent reports, including the present series, have described good results after combined aortic and renal artery reconstruction with <5% mortality rates, which are comparable to those observed after isolated infrarenal aortic repair. [5][6][7][8][9][10][11] Mortality was 2.6% in the present series.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…14,21,25-27 Several recent reports, including the present series, have described good results after combined aortic and renal artery reconstruction with <5% mortality rates, which are comparable to those observed after isolated infrarenal aortic repair. [5][6][7][8][9][10][11] Mortality was 2.6% in the present series.…”
Section: Discussioncontrasting
confidence: 40%
“…However, it should be stressed that improved hypertensive control has been reported in 50 to 70% of cases in the literature. 2,6,8,10,19,26,27,31 Kulbaski et al 10 demonstrated the value of empirical reconstruction of the renal artery in combination with aortic repair in patients under intensive antihypertensive medical regimens. In our series, disappearance or improvement of hypertension was achieved in 17 (61%) of the 28 patients presenting this symptom preoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ARAS is often accompanied by vascular disease in at least 1 additional arterial bed, namely PAD [142,143,144,145,146], abdominal aortic disease [146,147,148,149], carotid artery disease [145,150,151,152] and/or CHD [2, 114, 116, 152, 153]. This was recently verified in a cohort of patients with CHD.…”
Section: Discussionmentioning
confidence: 92%
“…However, it was not until 1952 that Freeman by performing disobliteration proved the superiority of the reconstructive operations over the nephrectomy. Despite the significant improvement in recent years in diagnosis as well as therapeutic procedures, patients with simultaneous arteriosclerotical alternations of the aorta and arterial hypertension still seem to be a major therapeutic problem [2].…”
Section: Introductionmentioning
confidence: 99%